The Cape Verdean Race: Identity-building in a suburban council estate - Mourão,Ana Luísa (2012)
This article explores local articulations of identity among Cape Verdean descendants in a council estate near Lisbon. The argument addresses their notions of Cape Verdeanness and Africanness, analysing how these are built and sustained in opposition to the Portuguese. It begins by pinpointing weak transnational (material and symbolic) ties with Cape Verde, moving to highlight widespread racism in Portugals political, media and social responses to African immigrants. Finally, it examines Cape Verdeans identity constructions, arguing that the categories, tacit meanings and group attributes they forge speak less of feelings of belonging to Cape Verde than of a looping effect whereby discursive elements of racism and segregation in Portuguese society are appropriated and reworked by the subjects themselves.